Varying cultivation strategies in eastern Tianshan corresponded to growing pastoral lifeways between 1300 BCE and 300 CE - Tian, Duo; Sun, Yufeng; Ritchey, Melissa M.; Xi, Tongyuan; Ren, Meng; Ma, Jian; Wang, Jianxin; Zhao, Zhijun; Ling, Xue; Liu, Xinyi (Frontiers in Ecology and Evolution, 2022)
This study combines plant stable isotope and archaeobotanical analyses to explore how ancient pastoral communities in varying landscapes of eastern Tianshan managed their barley fields. The latter is less archaeologically investigated, as recent discussions have focused on pastoral and nomadic activities. Results show that diversified cultivation strategies were employed in barley cultivation at different locations in eastern Tianshan. We also observed a diachronic transition towards less labor-intensive crop management corresponding to a growing pastoral lifeway from the late Bronze Age (1300-800 BCE) to historical periods (400 BCE-300 CE). These results inform us about the mechanism by which southwest Asian originated domesticates were adapted to the Inner Asian environments in the context of the early food globalization.